Guidelines for Designing IoT Applications for Older Adults - Rodrigues, Sandra Souza; Fortes, Renata Pontin de Mattos; Rodrigues, Kamila Rios da Hora (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC); 2024: Anais do XXIII Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais, 2024)
The Internet of Things (IoT) has emerged as a topic of significant interest within the Human-Computer Interaction (HCI) field. This new technological paradigm is transforming how individuals experience and utilize technology. Billions of everyday devices will be connected, and new forms of interaction will emerge with this new paradigm. However, the future role of IoT in terms of inclusion within intelligent environments raises questions regarding its ability to meet the needs of older adults. Population aging is a global phenomenon occurring at an accelerated pace, making it imperative for older individuals (60+) to be able to use technologies such as IoT. In this context, design guidelines are crucial, providing explicit recommendations for developing IoT applications that are intuitive and suitable for older adults. Thus, the thesis summarized in this work presents a set of guidelines to support designers and developers in creating IoT solutions tailored to older adults, taking into account accessibility and usability requirements. We developed the guidelines based on a methodology that involved the following phases: exploratory, experimental, descriptive, correlational, selection, specification, validation, and refinement. Various studies were conducted in each phase, including systematic mapping, snowballing, observation, interviews with older adults and companies, expert evaluations, development of proof-of-concept prototypes, and user evaluations with elderly participants. These phases and artifacts resulted in the Internet of Things - Applications Design Guidelines for the Elderly, entitled IoT_DGE 2.1, in its final version. Evaluation results demonstrated that the IoT_DGE 2.1 guidelines effectively assist in developing IoT applications, as developers utilizing these guidelines more successfully addressed accessibility and usability issues for older adults. The contributions of the thesis are detailed in various dimensions in this manuscript.